2018
DOI: 10.33369/jk.v2i2.8738
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Kebugaran Jasmani Berdasarkan Indeks Massa Tubuh Pada Siswa SMP Negeri 29 Bengkulu Utara

Abstract: Abstrak Penelitian ini bertujuan untuk mengetahui tingkat kebugaran jasmani berdasarkan indeks massa tubuh pada siswa SMP Negeri 29 Bengkulu Utara. Penelitian dilakukan dengan melakukan tes kebugaran jasmani dan tes antropometri pada siswa SMP Negeri 29 Bengkulu Utara. Sampel penelitian ini diambil dengan teknik Cluster Sampling. Analisis data yang di gunakan dalam penelitian ini adalah menggunakan persentase untuk menggambarkan frekuensi dan persentase dari data yang diperoleh. Hasil penelitian menyatakan bah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
0
10
0
16
Order By: Relevance
“…In spadateknokrat.ac.id, there is material content that is explained in detail with slides for teaching lecturers and is given a learning video recorded by the lecturers theirselves to discuss in detail the lecture material, in addition to material and video, there is a discussion forum column that functions to interact with questions and answers between students and lecturers if there are students who have not mastered the material well, in the last column there is a post test which is useful for measuring the level of student knowledge in each material that has been delivered. E-learning in Sports and Health Physical Education learning becomes more creative, because considering the large number of smartphone ownerships in students in this modern era, this makes learning taught to be more effective and for teachers this advantage of e-learning provides innovation for learning models which is more contemporary or modern than the material conveyed by the teacher during the lecture learning model (Prasetio, Sutisyana, Ilahi, & Defliyanto, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In spadateknokrat.ac.id, there is material content that is explained in detail with slides for teaching lecturers and is given a learning video recorded by the lecturers theirselves to discuss in detail the lecture material, in addition to material and video, there is a discussion forum column that functions to interact with questions and answers between students and lecturers if there are students who have not mastered the material well, in the last column there is a post test which is useful for measuring the level of student knowledge in each material that has been delivered. E-learning in Sports and Health Physical Education learning becomes more creative, because considering the large number of smartphone ownerships in students in this modern era, this makes learning taught to be more effective and for teachers this advantage of e-learning provides innovation for learning models which is more contemporary or modern than the material conveyed by the teacher during the lecture learning model (Prasetio, Sutisyana, Ilahi, & Defliyanto, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In normal BMI status, fit 1 times 1 times higher than in obese BMI status. In obese BMI status, the level of physical fitness category is less (Prasetio et al, 2018). Supported by research on 75 students, that the percentage of body fat and BMI has an inverse correlation with the value of VO2 max and flexibility.…”
Section: Table 7 Data Of Physical Fitness Based On Imtmentioning
confidence: 99%
“…Previous research concluded that there is a strong relationship between physical activity and fitness level and between BMI and fitness level also has a strong relationship (Alamsyah et al, 2017). The higher the BMI, the lower the physical fitness (Prasetio et al, 2018). BMI is a simple technique to easily find out a person's nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…Components of physical fitness are determinants of the degree of condition of each individual. Someone said to be fit if able to do all the activities of daily life without experiencing significant obstacles and can do the next task immediately (Prasetio et al, 2018). As for someone who is fit in relation to sports and physical activity is defined as a person who is able to carry out daily life without exceeding the limits of stress resistance in the body and has a healthy body and is not at risk of experiencing illness due to low levels of fitness or lack of physical activity (Endang Rini Sukamti, 2016).…”
Section: Introductionmentioning
confidence: 99%